The Impact of Working Capital Management on Firm Profitability An Empirical Study of Food and Beverage Companies Listed on the Amman Stock Exchange (Damascus University Journal for the economic and Political sciences, 2024)
The research aims to accurately determine the nature of the relationship between working capital management and corporate profitability. To achieve this goal, we used a comprehensive census method to study all agribusinesses listed on the Amman Stock Exchange for the period 2010-2020, and we relied on the cash conversion cycle to measure the management of the working capital and rate of return on assets to measure profitability. We also isolated the effect of a group of control variables: company size, financial leverage, liquidity ratio and sales growth. The results of the study showed that the management of working capital, measured by the cash conversion cycle, has a negative and significant effect on the profitability of companies. As for the effect of the components of the cash conversion cycle on profitability, it was not the same. Although the effect of the average collection period is negative, we find that the effect of each of the average inventory period and the average payment period on profitability is positive, noting that the effect of these three components on profitability was not significant
Keywords: Working Capital; Profitability; Liquidity